A double-end-beam based infrared device fabricated using CMOS-MEMS process. Issue 3 (20th June 2016) - Lei, Cheng; Mao, Haiyang; Yang, Yudong; Ou, Wen; Xue, Chenyang; Yao, Zong; Ming, Anjie; Wang, Weibing; Wang, Ling; Hu, Jiandong; Xiong, Jijun
Abstract : Purpose: Thermopile infrared (IR) detectors are one of the most important IR devices. Considering that the surface area of conventional four-end-beam (FEB)-based thermopile devices cannot be effectively used and the performance of this type of devices is relatively low, this paper aims to present a double-end-beam (DEB)-based thermopile device with high duty cycle and performance. The paper aims to discuss these issues. Design/methodology/approach: Numerical analysis was conducted to show the advantages of the DEB-based thermopile devices. Findings: Structural size of the DEB-based thermopiles may be further scaled down and maintain relatively higher responsivity and detectivity when compared with the FEB-based thermopiles. The authors characterized the thermoelectric properties of the device proposed in this paper, which achieves a responsivity of 1, 151.14 V/W, a detectivity of 4.15 × 108 cm Hz1/2/W and a response time of 14.46 ms sensor based on DEB structure. Orginality/value: The paper proposed a micro electro mechanical systems (MEMS) thermopile infrared sensor based on double-end-beam structure.